High school musical lasting impressions - Harper, Suzanne; Barsocchini, Peter 1952- (New York Disney Press, 2008)
"When Ms. Darbus announces plans for a new musical, Troy and Gabriella are thrilled to sing together again. But what if one of them doesn't make the cut? Then the drama hits a high note when Ms. Darbus reveals that a big-time talent scout will be attending the performance. It will take Troy, Gabriella, Taylor, Ryan, Chad, Sharpay, and the other Wildcats to make an amazing impression!"--P. [4] of cover
"Based on the Disney Channel original movie 'High School Musical,' written by Peter Barsocchini. Based on the Disney Channel original movie 'High School Musical 2,' written by Peter Barsocchini. Based on characters created by Peter Barsocchini."
"Disney Channel."
At head of title : Disney
English stories
1 14
Keywords: Friendship -- Juvenile fiction; High school students -- Juvenile fiction; High schools -- Juvenile fiction; Musicals -- Juvenile fiction; Schools -- Juvenile fiction; Graphic novels